POLYELECTROLYTES AND IST BIOLOGICAL PROPERTIES - Karahan, Mesut; Tuglu, Sevecen; Akdeste, Zeynep Mustafaeva (YILDIZ TECHNICAL UNIV, 2013)
The interaction of polymers having the characteristics of synthetic or natural, biocompatible and biodegradable polyelectrolytes with biomolecules exhibits the presence of biologically important mechanisms and has a great importance for biomedical uses. Researches about artificial immunization systems are still continuing thanks to the adjuvant effect which stimulates the immunity and which is one of the most important features of polyelectrolytes. In addition, synthesis of polyelectrolytes' conjugate and complexes, lighting of their structures, examination of their biological effects are still being developed. In this study, after giving general information about polyelectrolytes and their properties by presenting a general review of the preferred studies in artificial polymeric vaccine systems, it is intented to give information about their properties, importance and working principles in immunology.
Keywords: Polyelectrolyte; protein; bioconjugate; biomolecules; immunology; WATER-SOLUBLE COMPLEXES; PERFORMANCE LIQUID-CHROMATOGRAPHY; BOVINE-SERUM-ALBUMIN; TERNARY COMPLEXES; POLYACRYLIC-ACID; PROTEINS; POLYAMPHOLYTE; COPPER(II); PEPTIDES; KINETICS; Engineering